Comparison of bridge design in Malaysia between American codes and British codes [compact dict] - 348903 Wan Ikram Wajdee Wan Ahmad Kamal (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2005